A Low Power MOSFET-C Filter For Low Frequency Applications With Polynomial Regressive Design - (:unkn) unknown (IEEE, 2017)
In this work, a novel current mode MOSFET-C filter is proposed for a wide range of low frequency applications from biomedical signal sensing up to speech processing region. Presented filter consumes only 2.3 mu W under 1V supply voltage. Besides, proposed filter is given with novel design methodology based on polynomial regressive small signal models. In this way, promising interaction between design parameters such as V-GS, V-DS, channel width (W) and channel length (L) and filter specs such as f(0), Q and power is provided. Simulation results in 0.18 mu m CMOS technology are given and proposed filter is tested to process a real fetal PCG signal. It is shown that proposed filter attains a promising performance in comparison with the previously presented counterparts for low frequency applications.
Keywords: BANDPASS FILTER